2014
DOI: 10.1016/j.toxlet.2014.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide responsive miR153 targets Nrf2/ARE cytoprotection in paraquat induced dopaminergic neurotoxicity

Abstract: Epidemiological and animal studies suggest that environmental toxins including paraquat (PQ) increase the risk of developing Parkinson's disease (PD) by damaging nigrostriatal dopaminergic neurons. We previously showed that overexpression of a group of microRNAs (miRs) affects the antioxidant promoting factor, Nrf2 and related glutathione-redox homeostasis in SH-SY5Y dopaminergic neurons. Although, dysregulation of redox balance by PQ is well documented, the role for miRs and their impact have not been elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 79 publications
2
43
0
Order By: Relevance
“…Forced expression of miR-153 diminished GCLC and GSR expression, which resulted in alteration of Nrf2-dependent redox homeostasis (Narasimhan et al, 2012). Paraquat and H 2 O 2 have also been reported to significantly increase the expression of brain-enriched miR-153 with an associated decrease in Nrf2, ARE activity and expression of GCLC and NQO1 (Narasimhan et al, 2014). In our study, we found miR-153 was also significantly increased by 6-OHDA, and accounted for the reduction of Nrf2, which elicited a post-transcriptional repression of Nrf2 and its activity in dopaminergic SH-SY5Y neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forced expression of miR-153 diminished GCLC and GSR expression, which resulted in alteration of Nrf2-dependent redox homeostasis (Narasimhan et al, 2012). Paraquat and H 2 O 2 have also been reported to significantly increase the expression of brain-enriched miR-153 with an associated decrease in Nrf2, ARE activity and expression of GCLC and NQO1 (Narasimhan et al, 2014). In our study, we found miR-153 was also significantly increased by 6-OHDA, and accounted for the reduction of Nrf2, which elicited a post-transcriptional repression of Nrf2 and its activity in dopaminergic SH-SY5Y neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Once specific CDNA was generated, individual miRNA was detected using Tagman small RNA assay Real-time PCR analysis. Results were normalized to small nuclear RNA U6 and the data were expressed as Log 2-fold-change in respective miRs/U6 snRNA levels (Narasimhan et al, 2014).…”
Section: Rna Extraction and Real-time Pcrmentioning
confidence: 99%
“…Interestingly, miR-153 has been found enriched in the brain, pointing out a pivotal role of this miR in the redox homeostasis of the brain. Moreover, the same group demonstrated that miR-153 was increased after exposure to paraquat (PQ), an herbicide that causes irreversible damages to DA neurons and therefore is considered to be a potent risk factor of developing PD [161]. The neurotoxicity of PQ is attributed to the ROS generation and consequent induction of oxidative stress.…”
Section: Nrf2 and Mirnas In Parkinson's Diseasementioning
confidence: 99%
“…Of interest, PQ significantly increases, through a mechanism H 2 O 2 -dependency, the expression of miR-153 in neuronal cells that, in turn, reduces both Nrf2 expression and activity. Conversely, the overexpression of an anti-miR-153 prevents ROS accumulation as H 2 O 2 -induced neuronal death [161]. Interestingly, both miR-7 and miR-153 are also implicated in the post-transcriptional regulation of α-Syn by binding specifically its 3'-UTR [158,162].…”
Section: Nrf2 and Mirnas In Parkinson's Diseasementioning
confidence: 99%
“…BCRP/ABCG2, another important efflux transporter in ADME and MDR, is also regulated by a number of miRNAs via direct or indirect mechanisms ( Table 2). The MDR of S1 colon carcinoma cell line is Zhao et al, 2008;Guttilla et al, 2012;Wei et al, 2014a Let-7 Reporter assay, mRNA/protein expression, and function study Zhao et al, 2011 miR-18a Reporter assay, protein expression, association and function study Liu et al, 2009 miR-18a/b, -19b, -20b, -193b, -206 Reporter assay, protein expression Castellano et al, 2009;Leivonen et al, 2009b miR-145 Reporter assay, mRNA and protein expression, and function study Spizzo et al, 2010 miR-22 Reporter assay, protein expression, and function study Pandey and Picard, 2009;Xiong et al, 2010 miR-206 Reporter assay, protein expression, and function study Adams et al, 2007;Kondo et al, 2008 miR-27a via zinc finger and BTB domain containing 10 (ZBTB10) Li et al, 2010a miR-219-5p Reporter assay, mRNA/protein expression, association and function Huang et al, 2015 miR-135b Reporter assay, mRNA and protein expression Aakula et al, 2015 NFE2L2/Nrf2 miR-144 Reporter assay, mRNA and protein expression, and function study Sangokoya et al, 2010 miR-28 Reporter assay, mRNA and protein expression Yang et al, 2011 miR-200a (Activation) via Kelch-like ECH-associated protein 1 (Keap1) Eades et al, 2011;Yang et al, 2014 miR-153, -27a, -142-5p, -144 Reporter assay, mRNA and protein expression, and function study Narasimhan et al, 2012Narasimhan et al, , 2014 Protein expression, and function study Singh et al, 2013 miR-507, -634, -450, -129-5p Reporter assay, mRNA and protein expression, and function study Yamamoto et al, 2014 miR-34a mRNA and protein expression Huang et al, 2014 miR-340 Reporter assay, mRNA and protein expression, and function study Shi et al, 2014a miR-141 via Kelch-like ECH-associated protein 1 (Keap1) …”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 99%